New species of Duplominona Karling, 1966 (Platyhelminthes, Proseriata) from the Pacific coast of Panama - Curini-Galletti, Marco; Carcupino, Marcella; Stocchino, Giacinta A.; Leasi, Francesca; Norenburg, Jon L. (Zootaxa, 2020)
Eight new species of Duplominona (Platyhelminthes, Proseriata, Monocelididae) are described from the Pacific coast of Panama. They differ from their congeners in the detailed morphology of hard structures associated with the copulatory organ. Duplominona basidilatata n. sp. has a cirrus provided with 5–6 rows of triangular spines, 3–8 μm long, with a large, flat, poorly sclerotized basis. D. hystricina n. sp. has 10–12 rows of needle-shaped spines, 3.5–15 μm long, with a swollen basis. The cirrus of D. hyperhystricina n. sp. is provided with 20–25 rows of slender spines 1.5–9 μm long, with a recurved distal tip. In D. veracruzensis n. sp., cirrus spines increase abruptly in size, from 1.5–2 μm to 6–7 μm. D. uniserta n. sp. has a very long seminal vesicle and a small cirrus, provided with one girdle of hook-shaped spines, 3–5 μm long. D. macrodon n. sp. has one girdle of large, triangular spines, 8–18 μm long. Both D. trimera n. sp. and D. pseudotrimera n. sp. have a tripartite tail, and their cirrus is provided with a stylet. In D. trimera n. sp., the stylet is surrounded by 15–20 rows of spines, 6.5–10 μm long, while D. pseudotrimera n. sp. has 6–8 rows of large spines, 7–22 μm long. D. uniserta n. sp. and D. aduncospina Curini-Galletti, 2019 from the Caribbean coast of Panama have few rows of morphologically nearly identical spines, and are possible candidates as trans-isthmian geminate species. The presence of species with a tripartite tail on both sides of the Isthmus of Panama suggests the possibility of further geminate species pairs; however, no support could be obtained on the basis of the morphology of their hard structures. Five of the eight new species of Duplominona have been found in a single locality, and the diversity of genus along the Pacific coast of Panama may be far higher than present contribution suggests.